2010
DOI: 10.1017/s0007114509993667
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a therapeutic agent: the evidence fromin vitro, animal and human studies

Abstract: Curcumin is the active ingredient of turmeric. It is widely used as a kitchen spice and food colorant throughout India, Asia and the Western world. Curcumin is a major constituent of curry powder, to which it imparts its characteristic yellow colour. For over 4000 years, curcumin has been used in traditional Asian and African medicine to treat a wide variety of ailments. There is a strong current public interest in naturally occurring plant-based remedies and dietary factors related to health and disease. Curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
326
0
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(339 citation statements)
references
References 155 publications
(192 reference statements)
3
326
0
10
Order By: Relevance
“…Curcumin facilitates excretion of many oxygen radicals, particularly superoxide anion, nitrogen dioxide, and hydrogen radicals. [18,19] Although it is difficult to create a supportive treatment environment similar to that applied in intensive care units in animal models, experimental models are of great importance in understanding the physiopathology of septic shock and finding new therapeutic approaches prior to clinical trials. The CLP model used in the present study creates a model similar to the clinical features of septic shock and resembles human sepsis, as the CLP model displays hypodynamic and hypometabolic phases following the hypermetabolic phase.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…Curcumin facilitates excretion of many oxygen radicals, particularly superoxide anion, nitrogen dioxide, and hydrogen radicals. [18,19] Although it is difficult to create a supportive treatment environment similar to that applied in intensive care units in animal models, experimental models are of great importance in understanding the physiopathology of septic shock and finding new therapeutic approaches prior to clinical trials. The CLP model used in the present study creates a model similar to the clinical features of septic shock and resembles human sepsis, as the CLP model displays hypodynamic and hypometabolic phases following the hypermetabolic phase.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…Curcum (CUR) is an intensely yellow pigment, isolated from rhizomes of Curcuma longa, which is in worldwide used as a cooking spice, flavoring agent, and colorant [22]. An increasing number of investigations have suggested that CUR exhibits potential therapeutic applications that may be enhanced by combination with light, as it displays a high light absorption in the visible spectral region, around 400-500 nm [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric, the powdered rhizome of Curcuma longa L., has been used to treat a variety of inflammatory conditions and chronic diseases (Ammon & Wahl, 1991). Curcumin (CUR) is a naturally occurring, intensely yellow turmeric pigment that it is in worldwide use as a cooking spice, flavoring agent and colorant (Epstein et al, 2010). An increasing number of investigations have suggested that CUR exhibits potential therapeutic applications such as anti-inflamatory, antioxidant, antimicrobial, antifungal and anticancer properties (Epstein et al, 2010;Martins et al, 2009).…”
Section: Evaluation Of the Antitumor Potential Of Curcumin-mediated Pdtmentioning
confidence: 99%
“…Curcumin (CUR) is a naturally occurring, intensely yellow turmeric pigment that it is in worldwide use as a cooking spice, flavoring agent and colorant (Epstein et al, 2010). An increasing number of investigations have suggested that CUR exhibits potential therapeutic applications such as anti-inflamatory, antioxidant, antimicrobial, antifungal and anticancer properties (Epstein et al, 2010;Martins et al, 2009). Some studies also showed that CUR inhibits chemically induced carcinogenesis in the skin, forestomach, and colon when it is administered during initiation and/or postinitiation stages (Kawamori et al, 1999;Huang et al,1994).…”
Section: Evaluation Of the Antitumor Potential Of Curcumin-mediated Pdtmentioning
confidence: 99%